Canicular sialolithectomy of a giant sialolith - Sair Andrés Miquet Vega; Yoimar Deronceré Columbié (Editorial Ciencias Médicas, 2020)
Introduction: Sialolithiasis is a common disorder of the major salivary glands which presents more frequently in male patients. Objective: Present a clinical case of sialadenitis due to sialolithiasis of the submandibular gland successfully treated by intraoral canicular sialolithectomy. Case report: A male 45-year-old patient attending the Maxillofacial Surgery Department at Manuel de Jesús Cedeño Specialty Clinic in Granma, Cuba, presents with discomfort on the floor of the mouth and a hard, mobile and easily movable mass of increased volume. Radiographic examination revealed a radiopaque oval-shaped image of well-defined edges, approximately 4 cm long x 2 cm wide. A diagnosis was made of sialadenitis due to sialolithiasis of the right submandibular gland. Symptoms were treated with analgesics / anti-inflammatories and antibiotics. Intraoral canicular sialolithectomy was performed. Rechanneling of the duct was then conducted to allow permeabilization. Conclusions: Sialadenitis due to sialolithiasis is a condition of a favorable prognosis. Appropriate treatment will have the gland return to its normal physiology, improving the patient's quality of life. In our case, surgical removal was conducted by intraoral canicular sialolithectomy without any complications. The patient had completely recovered after one month's evolution, the treatment being satisfactory both short- and long-term.